Women's Representation in Policy Making at the Local Level in Indonesia - Romadhan, Ach. Apriyanto; Sihidi, Iradhad Taqwa; Hardini, Hevi Kurnia; Ermylina, Eva (Journal Public Policy, 2025)
This study aims to examines the substantive political representation of women in the Malang City Regional Representative Council (DPRD) during the policy-making process of the Draft Regional Regulation (Ranperda) on the 2022–2042 Regional Spatial Plan (RTRW). Using a qualitative research design with a literature review and document analysis covering DPRD minutes, the draft Ranperda, and faction structure, this study explores how gender, educational attainment, and institutional hierarchy shape the substantive participation of female legislators. The findings reveal that although women's descriptive representation in the Malang City DPRD has increased to 26.66%, their involvement in strategic decision-making remains limited. Male legislators continue to dominate influential positions such as faction chairperson, advisor, spokesperson, and membership in Special Committees (Pansus), leaving women largely confined to administrative or peripheral roles. Despite showing a higher attendance rate (93%) compared to men (83%), the substantive contribution of female legislators is significantly lower (41.67% vs. 75.76%). Educational background enhances engagement among female legislators, yet gendered structures and cultural norms continue to constrain their influence. This study concludes that women’s representation in Malang’s DPRD remains paradoxical, as educational advantages enhance engagement but structural and cultural barriers continue to limit their substantive policy influence.This study aims to examines the substantive political representation of women in the Malang City Regional Representative Council (DPRD) during the policy-making process of the Draft Regional Regulation (Ranperda) on the 2022–2042 Regional Spatial Plan (RTRW). Using a qualitative research design with a literature review and document analysis covering DPRD minutes, the draft Ranperda, and faction structure, this study explores how gender, educational attainment, and institutional hierarchy shape the substantive participation of female legislators. The findings reveal that although women's descriptive representation in the Malang City DPRD has increased to 26.66%, their involvement in strategic decision-making remains limited. Male legislators continue to dominate influential positions such as faction chairperson, advisor, spokesperson, and membership in Special Committees (Pansus), leaving women largely confined to administrative or peripheral roles. Despite showing a higher attendance rate (93%) compared to men (83%), the substantive contribution of female legislators is significantly lower (41.67% vs. 75.76%). Educational background enhances engagement among female legislators, yet gendered structures and cultural norms continue to constrain their influence. This study concludes that women’s representation in Malang’s DPRD remains paradoxical, as educational advantages enhance engagement but structural and cultural barriers continue to limit their substantive policy influence.